Anticancer Properties of Curcumin Against Colorectal Cancer: A Review - Ojo, Oluwafemi Adeleke; Adeyemo, Temiloluwa Rhoda; Rotimi, Damilare; Batiha, Gaber El-Saber; Mostafa-Hedeab, Gomaa; Iyobhebhe, Matthew Eboseremen; Elebiyo, Tobiloba Christiana; Atunwa, Bukola; Ojo, Adebola Busola; Lima, Clara Mariana Goncalves; Conte-Junior, Carlos Adam (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is one of the most common and reoccurring diseases, as well as the world's second largest cause of mortality. Despite existing preventative, diagnostic, and treatment methods, such as chemotherapy, the number of instances rises year after year. As a result, new effective medications targeting specific checkpoints should be developed to combat CRC. Natural compounds, such as curcumin, have shown significant anti-colorectal cancer characteristics among medications that can be used to treat CRC. These chemicals are phenolic compounds that belong to the curcuminoids category. Curcumin exerts its anti-proliferative properties against CRC cell lines in vitro and in vivo via a variety of mechanisms, including the suppression of intrinsic and extrinsic apoptotic signaling pathways, the stoppage of the cell cycle, and the activation of autophagy. Curcumin also has anti-angiogenesis properties. Thus, this review is aimed at emphasizing the biological effect and mode of action of curcumin on CRC. Furthermore, the critical role of these substances in CRC chemoprevention was emphasized.